Locally advanced thyroid cancer: case report - R. I. Azizyan; O. A. Saprina; A. Kh. Bekyashev; D. S. Belov; T. G. Gasparyan; E. S. Gorobets; V. V. Balandin; G. V. Ungiadze; E. L. Dronova; A. V. Vasil’ev; M. V. Lomaya (Опухоли головы и шеи, 2016)
The paper gives the results of treatment in a female patient with locally advanced thyroid cancer with a tumor thrombus in the internal jugular vein with laryngeal or tracheal involvement, and a giant metastasis into the bone of the vault of the skull.